Notes on Malta Fever in Lima - Rebagliati, Raúl (1922)
In recent years, some national researchers have revealed the existence of Malta Fever in certain localities of Peru. In 1910, Barton was first described in a case of this Lima infection proven by culture. Velez Lopez in 1913, noted the presence of some patients in Trujillo. Then it has not published anything on the subject.